حماية حقوق المرأة في منظور التشريع الإماراتي والاتفاقيات والمعاهدات الدولية - خليفه محمد عبيد راشد عبود; Khalifa Mohamed Obaid Rashid Aboud (Universiti Sains Islam Malaysia, 2024)
Matric: 4201415 (FSU)